The quality of public finances - Michael Thöne (Finanzwissenschaftliches Forschungsinstitut an der Universität zu Köln (FiFo Köln), 2022)
The concept of the "quality of public finances" (QPF) covers many qualitative and structural issues of fiscal policy. This chapter traces the origins of the concept of QPF to the Lisbon Strategy and the subsequent EPC Working Group on "Quality of Public Finances" (2004-2007). At its core, the QPF focuses on the impact that the composition of public spending has on long-term goals such as economic growth. Growth- and sustainability-enhancing public spending comprises infrastructure investment, human capital investment (education, health, family policy, gender policy) and spending on natural capital and climate protection. Today, QPF indicators can very helpful in national fiscal governance and for the supranational surveillance as in the EU. A future QPF approach for the 2020s should help to prioritize inclusive growth and decoupling economic growth from the use of finite resources. Quality indicators can also help to determine the legit- imate levels of new government debt ("green golden rule").
Keywords: E62; H11; H50; H52; H54; H61; 330; Quality of public finances (QPF); expenditure composition; growth-enhancing public spending; fiscal governance; decoupling; green golden rule